Analisis Hubungan Kompetensi Pedagogik Guru Terhadap Kemampuan Literasi Budaya dan Kewargaan Pada Pelajaran PPKn - Erwin Simon Paulus Olak Wuwur; Dwi Yani; Ahmad Saifullah; Nine Sekumi Hasiholan (International Forum of Researchers and Lecturers, 2023)
There are still many challenges in the world of education in Indonesia, so that the goals of education have not been fully realized. one of the problems in Indonesian education is that learning outcomes at the elementary and secondary school levels are very minimal due to an imbalance in the effectiveness of learning and learning in the classroom. In 2019, the average teacher competency score (UKG) was 57 out of 100, with a teacher pedagogical average of 49.34 and a teacher professional average. The low literacy and competence of teachers is a benchmark for the success of education in Indonesia. This study aims to analyze the relationship between a teacher's pedagogical competence and students' cultural literacy and citizenship abilities through PKN subjects. The method used in this research is descriptive-qualitative, with the subject being a class V teacher and students at an elementary school in Mojokerto. The results of the study show that there is a relationship and influence between the pedagogical competencies possessed by teachers on the cultural literacy and citizenship abilities of students in PKN subjects. This can be seen from the readiness of the teacher to design and design learning tools, implementing learning in the classroom to evaluating learning.